The Effectiveness of Paradoxical Psychotherapy on Trichotillomania Disorder - Zahmatkesh, Hossein; Asayesh, Mohammad Hassan (KMAN Counseling & Psychology Nexus, 2026)
Trichotillomania is a subtype of obsessive-compulsive related disorders characterized by recurrent hair pulling and inability to control the behavior, leading to various physical and psychological consequences. Considering the limited effectiveness of current treatments and the need for innovative approaches, the present study aimed to evaluate the effectiveness of Paradoxical Psychotherapy like PTC model in reducing symptoms of trichotillomania. In In this single-group quasi-experimental time-series, 17 women with symptoms of trichotillomania were selected through purposive sampling. The intervention consisted of five sessions based on the PTC model, and assessments were conducted at four stages (baseline, Third session, post-treatment, and two-month follow-up) using the Massachusetts General Hospital Hairpulling Scale (MGH-HS) and the Treatment Outcome Subjective Rating Scale (TOSRS). Data were analyzed using repeated measures ANOVA and Friedman test. Findings showed that Paradoxical psychotherapy significantly reduced trichotillomania symptoms over time (η²=0.85, p